HAKIKAT PERSETUJUAN MAJELIS KEHORMATAN NOTARIS SEBAGAI UPAYA PERLINDUNGAN HUKUM PADA NOTARIS DALAM PROSES PERADILAN - Hery Kurniawan Zaenal (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
This study aims to: (1) analyze and discover the nature of the approval of the Notary Honorary Council as an effort to protect the law against notaries in the judicial process; (2) Analyze and find law enforcement for Notaries related to Professional Ethics. This type of research is normative law. While the research approach used, namely: Legislation, conceptual approach, and case approach, as well as a comparative approach. The legal materials used in this study are primary legal materials and secondary legal materials. While the analysis of legal materials using qualitative analysis. The results of the study show that: (1) The regional MKN has the authority to examine applications submitted by investigators, public prosecutors or judges; as well as giving approval or rejection of requests for approval to take photocopies of minuta deed and summons Notaries to attend investigations, prosecutions, and judicial processes (66 paragraph (1) UUJNP), (2) Sanctions imposed on Notaries who violate the professional code of ethics are regulated in Article 85 UUJN, namely in the form of: Verbal warning; Written warning; temporary stop; Honorable discharge; and Dishonorable Dismissal by the Notary Honorary Council.